THE EFFECT OF WOUND CARE EDUCATION ON FRACTURE PATIENTS IN AN EFFORT TO ACCELERATE THE WOUND HEALING PROCESS - Ernasari, Ernasari; Sudarman, Sudarman; Suryanti. S; Nadira Fit; Nur Jelita T Ahmad (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Postoperative fracture patients have a high risk of delayed wound healing due to limited knowledge and skills in performing independent wound care. Lack of knowledge about proper wound care techniques can increase the risk of infection, prolong the length of stay, and reduce the patient's quality of life. Therefore, structured wound care educational interventions are needed to improve patient understanding and optimize the wound healing process. This study aims to analyze the effect of wound care education on increasing knowledge and accelerating the wound healing process in postoperative fracture patients. This research method uses a quasi-experimental design with a pretest–posttest control group approach. A total of 40 postoperative fracture patients were divided into an intervention group (n=20) who received structured wound care education and a control group (n=20) who received standard education from Pelamonia Makassar Class II Hospital. The level of knowledge and wound healing conditions were measured before and after the intervention using a structured questionnaire and observation sheet. Data were analyzed using statistical tests with a significance level of 0.05. The results of this study showed an increase in knowledge scores in both groups, with a greater increase in the intervention group than in the control group. The wound healing process in the intervention group showed more significant improvement than in the control group. There is a significant relationship between increasing patient knowledge and accelerating the wound healing process (p<0.001). The conclusion of this study shows that structured wound care education has an impact on increasing the knowledge of fracture patients and contributes to accelerating the wound healing process. Hospitals need to include structured education as a permanent protocol in the SOP for fracture patients.